The Role of Innovation In the Economy of Uzbekistan - Khashimova Naima Abitovna; Buranova Manzura Abdukadirovna (European Journal of Life Safety and Stability (2660-9630), 2023)
This article analyzes the fact that innovation is becoming one of the most characteristic features of economic development and is a factor that accelerates market development. Also, proposals and recommendations are given that rapid development of entrepreneurship can be achieved through the wide use of innovations in the modern world.